Penerapan media augmented reality dalam pembelajaran tata krama bahasa Sunda pada siswa SMP Alfa Centauri kota Bandung - Nugraha, Haris Santosa; Sutisna, Ade; Garsela, Fajar; Sari, Erni Endah; Dzakiah, Shoofii Nurrizki (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
Learning about tata krama (etiquette) in Sundanese often faces obstacles, particularly due to the limited availability of instructional media that can realistically and comprehensively represent social situations. As a result, students struggle to distinguish and apply various speech levels—such as respectful, familiar, and harsh language—according to context. This study aims to examine the effectiveness of Augmented Reality (AR) technology in enhancing students’ understanding of Sundanese etiquette. A quantitative approach was employed using an experimental method with a pre-test post-test control group design. The study involved 44 seventh-grade students from SMP Alfa Centauri in Bandung. Data were collected through comprehension tests and analyzed using a paired sample t-test. The results showed a significance value of 0.00, indicating a significant difference between the pre-test and post-test scores in the experimental group. Furthermore, the N-Gain score of 0.73 suggests a high level of improvement in learning outcomes. These findings demonstrate that AR media can effectively visualize complex social communication interactions, thereby supporting deeper student comprehension. Thus, the integration of Augmented Reality proves to be an effective and innovative solution for technology-based Sundanese language learning.